Face-Off - Jake Maddox (Stone Arch Books, 2007)
Kyle wants to be a great hockey player just like his older brother, but to do that, he must focus all of his energy on the game and not be distracted by a teammate's injury.
Keywords: Sport Stories -- Sport Stories